Immunological memory 1 - Gray, David (Henry Stewart Talks, 2020)
Definition and function of immunological memory, Generation of immunological memory, Characteristics of memory B cells, Characteristics of memory T cells, Signals directing development of B and T cells, Detection of memory cells in vivo